PSI-16 Exploring the relationship between digesta retention time in the equine gastrointestinal tract and compartment models. (7th December 2018) - Hansen, T; Bobel, J; Rankins, E; Vasco, C; Sanchez, L; Warren, L
Abstract: Digesta retention time within specific segments of the equine gastrointestinal tract (GIT) may be more relevant to scientific inquiries than total tract mean retention time (TTMRT); however, measuring retention time in individual segments requires access to the digestive tract, either through GIT fistulas or via terminal studies. The objective of this study was to compare MRT in the foregut, cecum, and colon to model-derived compartment MRT. After a 10-d adaptation, a cannulated gelding was fed indigestible particulate and liquid markers to determine TTMRT. The gelding was dosed with different pairs of particulate and liquid markers into the cecum to determine hindgut MRT (HGMRT) and into the right ventral colon through the cecocolic orifice to measure large colon MRT (LCMRT). Fecal samples were composited in 2-h intervals for the first 60 h and 4-h intervals from 64 to 84 h post dose. The procedure was repeated 4 times over 60 d for 4 measurements of TTMRT, HGMRT, and LCMRT. Fecal marker concentrations were fit to stochastic and deterministic models using nonlinear least squares (MATLAB). Algebraic MRT and compartment MRT were compared using paired t-test (SAS) for each GIT segment and model. For liquid and particulate makers, the deterministic model TTMRT (17.5 ± 1.5 vs. 26.3 ± 1.8 h) differed ( P = 0.007 vs. P = 0.051) from algebraic TTMRT (29.0 ± 1.7 vs. 34.4 ± 3.7 h). Stochastic model exponential compartment MRT (5.8 ± 1.0 vs. 5.0 ± 0.4 h) were similar to foregut MRT (TTMRT – HGMRT; 7.4 ± 2.0 vs. 7.3 ± 0.9 h), but no similarities were observed between other compartment MRT and HGMRT or LCMRT. In these exploratory data, compartment retention times failed to pair with MRT in GIT segments. Significant methodological and analytical challenges remain to determine retention time in individual segments of the equine GIT.